A Book of Childrens Literature - Hollowell, Lillian (New York Holt, Rhinehart and Winston, Inc, 1966)
The purpose of this book is that of providing students, teachers, librarians, parents, and others interested in childrens reading a broad acquaintance with the various types of literature for children of different ages. The book aims, too, at conveying knowledge of the social and historical background from which childrens literature has developed; and at supplying criteria to help in the selection and evaluation of books for children. This book may be used as a text or as a sourcebook.
Keywords: Literature